Financial reform and the mobilization of domestic savings: The experience of Morocco - Mina Baliamoune-Lutz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Using a vector error-correction model, I explore the short-run dynamics and long-run linkages between financial reform and the mobilization of domestic saving in Morocco. In the short run, financial depth (volume of intermediation) is shown to have a positive influence on private saving, while increases in real interest rates have a negative impact. The effectiveness of financial intermediation does not seem to have a direct effect on saving but has a significant influence on the volume of intermediation. In the long run, savings have a stable relationship with financial reform but the influence of interest rates remains negative, implying that the income effect dominates in the long run as well.
Keywords: E21; E44; O16; 330; financial sector reform; Morocco; saving mobilization; VECM; Bankenpolitik; Finanzintermediär; Sparen; Sparförderung; Marokko